A systematic review and life cycle assessment of biomass pellets and briquettes production in Latin America. (April 2022) - Silva, D.A.L.; Filleti, R.A.P.; Musule, R.; Matheus, T.T.; Freire, F.
Abstract: The world market for solid biofuels has increased in the last few years, with special attention to the production of pellets and briquettes in emerging bioeconomies. This study presents a systematic review and exploratory Life Cycle Assessment (LCA) of biomass briquettes and pellets produced in Latin America, and suggests short-term opportunities and political implications. The review was organized following the scoping methodology en bloc with the Standardized Technique for Assessing and Reporting Reviews of Life Cycle Assessment Data - STARR-LCA, in Scopus, Web of Science and Scielo databases. A final list of 150 publications was selected. The review results showed that most of the publications were from Brazil, Colombia, Chile, Mexico and Costa Rica, and are mainly focused on exploring the thermo-mechanics properties of pellets and briquettes instead of the environmental impacts. Thus, an exploratory LCA was performed based on the data gathered from literature with a focus on global warming potential, terrestrial acidification potential, freshwater eutrophication potential, cumulative energy demand, land use and water consumption. Global warming results ranged from −68.7 (Chilean pellets) to 103 g CO2 -eq (Brazilian charcoal briquettes), and pellet productions showed lower values of impacts (−68.7 to 1.33 g CO2 -eq) per functional unit. The best scenario, however, was found for the Brazilian briquettes production contributing with less than 10% of the overall relative impacts for cumulative energy demand (0.340 MJ-eq), terrestrial acidification potential (8.59 mg SO2-eq), freshwater eutrophication potential (0.969 mg PO4 -eq), land use (136 cm 2 a crop-eq) and water consumption (108 cm 3 ), where urban forest residues were used as biomass. The worst-case scenario was found for the charcoal briquettes in Brazil and pellet productions from palm fruit branches in Colombia. Dedicated systems to the pellets/briquettes production seem to be more environmentally benign options than the multifunctional systems investigated. In terms of political implications, it was verified the great potential from these different types of densified biomass in improving and expanding emission trading systems both inside and outside Latin America. Highlights: LCA studies of biomass pellets/briquettes in Latin America were assessed. Brazil was the only Latin American country assessing biomass briquettes production. Global warming impacts ranged from −68.7 to 103 g CO2-eq. Dedicated production systems had lower impact results than multifunctional systems.